Microsatellite markers for evaluating the diversity of the natural killer complex and major histocompatibility complex genomic regions in domestic horses - Horecky, C; Horecka, E; Futas, J; Janova, E; Horin, P; Knoll, A (HLA, 2018)
Genotyping microsatellite markers represents a standard, relatively easy, and inexpensive method of assessing genetic diversity of complex genomic regions in various animal species, such as the major histocompatibility complex (MHC) and/or natural killer cell receptor (NKR) genes. MHC-linked microsatellite markers have been identified and some of them were used for characterizing MHC polymorphism in various species, including horses. However, most of those were MHC class II markers, while MHC class I and III sub-regions were less well covered. No tools for studying genetic diversity of NKR complex genomic regions are available in horses. Therefore, the aims of this work were to establish a panel of markers suitable for analyzing genetic diversity of the natural killer complex (NKC), and to develop additional microsatellite markers of the MHC class I and class III genomic sub-regions in horses. Nine polymorphic microsatellite loci were newly identified in the equine NKC. Along with two previously reported microsatellites flanking this region, they constituted a panel of 11 loci allowing to characterize genetic variation in this functionally important part of the horse genome. Four newly described MHC class I/III-linked markers were added to 11 known microsatellites to establish a panel of 15 MHC markers with a better coverage of the class I and class III sub-regions. Major characteristics of the two panels produced on a group of 65 horses of 13 breeds and on five Przewalski's horses showed that they do reflect genetic variation within the horse species.
Keywords: Major Histocompatibility Complex; natural killer complex; Killer Cells, Natural; genetické lokusy; mikrosatelitní repetice; microsatellite markers; genetic diversity; genetická variace; Animals, Domestic; Microsatellite Repeats; Horses; Genome; Genetic Variation; hospodářská zvířata; zvířata; horses; Breeding; koně; chov; genom; Genetic Loci; hlavní histokompatibilní komplex; buňky NK; major histocompatibility complex; Animals